Effect of Different Harvest Time and Microwave Aging on Aroma Characteristics of Japanese Apricot Wine - Aoting Li; Jiangfeng Song; Yike Wang; Xiao Huang; Silas Segbo; Zhihong Gao (Molecules)
The aroma and nutrition of Japanese apricot fruit change continuously as the fruit ripens. The differences in fruit aroma and nutrition can affect the resulting wine, which is produced by steeping the Japanese apricot fruit. In this study, we used HS-SPME-GC-MS to examine the aromatic compositions of Japanese apricot fruit and wine produced from its macerated fruit at different levels of ripeness. We employed UPLC to examine the nutritional components such as organic acids, amygdalin, and phenolics to support the identification of the optimal ripening time. The microwave aging technology was also used to treat the steeped mume wine in order to explore the optimal conditions for microwave aging. We found that the optimum aroma period for the ‘Nannong Longxia’ fruit was 81 d after flowering. Furthermore, the changes in the aroma of mume wine after steeping in 65%vol base wine were closer to those of the fruit than those of 42%vol base wine, and the optimum period for the aroma of mume wine after steeping was the same as the fruit. Analysis showed that the optimum nutritional period for the fruit coincided with the optimum aromatic period. The best aromatic and nutritional components of the finished wine were obtained when the fruit was picked 81 days after flowering and the steeped mume wine was made with a 65%vol base wine. Microwave aging technology can significantly increase the proportion of esters in the aroma composition and reduce the content of acids. Among them, 500 W treatment at 50 °C for 80 min had the best effect on improving aroma components. These findings represent a theoretical foundation for exploring the aroma optimum period for Japanese apricot fruit and steeped mume wine, and for determining the optimum harvest periods for production.